Investigation on transient behaviours of a uni-grounded low-voltage AC microgrid and evaluation on its available fault protection methods: Review and proposals. (August 2017) - Bui, Duong Minh; Chen, Shi-Lin; Lien, Keng-Yu; Chang, Yung-Ruei; Lee, Yih-Der; Jiang, Jheng-Lun
Abstract: In a general microgrid (MG), a step-up distribution transformer is used to facilitate integration of the low-voltage (LV) AC microgrid into a medium-voltage distribution system. On the other hand, isolation transformers are placed between distributed energy resources (DERs) (e.g. non-renewable/renewable energy resources and energy storage devices) and common AC buses/lines to eliminate DC-current components and to configure 3-phase & 4-wire, 3-phase & 3-wire, 1-phase & 2-wire, or 1-phase & 3-wire AC microgrids. When all neutral points of isolation transformers are grounded through a unique grounding system of the step-up distribution transformer, a uni-grounded AC microgrid structure is configured. This paper not only mentions advantages and shortcomings of the uni-grounded LVAC microgrid operation, but also investigates its transient operation characteristics. Transient simulation results of the uni-grounded LVAC MG are surveyed through various fault situations and operation transition tests between the grid-connected mode and the islanded mode of the microgrid. Available fault protection methods of a uni-grounded LVAC microgrid are considered. Transient simulation results from PSCAD software are used to validate the fault protection solutions developed for the uni-grounded LVAC microgrid. Last, a generalised fault protection system of uni-grounded LVAC microgrids is proposed in the paper. Highlights: Outline three different configurations of uni-grounded low-voltage AC microgrids. Review on existing fault protection solutions for the microgrid and fault analysis. Investigate transient and dynamic responses of an ungrounded AC microgrid (MG). Develop a generalised fault protection structure of uni-grounded AC microgrids. Evaluate protection coordination strategies and the electrical safety of the MG.